PSYCHOMETRIC EVALUATION AND MEASUREMENT INVARIANCE OF THE SOCIAL EMOTIONAL ASSETS AND RESILIENCE SCALE (SEARS) AMONG ADOLESCENTS - Saidi, Liley Afzani; Abdullah, Rayyan Cheong Tiang Ming; Ramlee, Siti Nurhafizah Saleeza; Yusof, Wan Sue Emi Yusnita Wan; Rahaman, Nur Haffiza (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
In the context of increasing awareness on youth resilience and emotional development, this study investigates the psychometric properties of the Social Emotional Assets and Resilience Scale – Adolescent Version (SEARS-A) among adolescents in urban settings. Specifically, it aims to (i) evaluate the factorial structure, internal consistency, and concurrent validity of SEARS-A, and (ii) examine its measurement invariance across gender, ethnicity, and caregiver background. A total of 115 adolescents aged 17 completed the SEARS-A, while 58 primary caregivers completed the SEARS-P to assess concurrent validity. Confirmatory factor analysis (CFA) using the WLSMV estimator supported the hypothesised four-factor model Self-Regulation, Empathy, Responsibility, and Communication showing good model fit and structural validity. Multi-group CFA confirmed configure, metric, and scalar invariance, demonstrating the scale’s psychometric stability across key demographic groups. Reliability analysis indicated high internal consistency across all subscales (α = .79–.87) and total score (α = .91). Concurrent validity was supported through significant positive correlations between adolescent and caregiver responses, while criterion validity was established via associations with the Behaviour Assessment System for Children Second Edition (BASC-2). Although overall psychometric performance was strong, several empathy items showed relatively lower factor loadings, highlighting the importance of cultural and contextual sensitivity in item construction. The findings suggest that SEARS-A is a robust and multidimensional instrument for assessing core social-emotional competencies among adolescents. Its validated structure, strong reliability, and invariance across diverse demographic profiles make it suitable for both applied interventions and empirical research. By capturing key psychological strengths, SEARS-A contributes to the broader efforts in youth mental health, educational planning, and resilience-building programs across diverse cultural and urban contexts.